Dynamics of Normal and Reverse Polarization Switching in 1550-nm VCSELs Under Single and Double Optical Injection - Salvide, Matias (2015)
Polarization switching (PS) in 1550nm-VCSELs under single and double pulsed polarized optical injection is investigated experimentally and in theory. ‘Normal’ and ‘reverse’ PS were achieved, respectively, when the device was subject to single and double optical injection. Speed operation enhancement is observed for ‘reverse’ PS under double polarized optical injection. Also, the minimum injection power requirements for both ‘normal’ and ‘reverse’ PS have been analyzed showing significant differences for the two investigated cases. Furthermore, we have also investigated numerically the influence of important system parameters, such as the normalized bias current, the injection field strength and the linewidth enhancement factor in the optimal operation conditions for both types of PS. Overall good agreement between theory and experiments is found.